Kolaborasi Inovatif FE UMMI dengan P3DW dalam Peningkatan Kesadaran dan Kepatuhan Pajak pada Siswa SLTA di Kota dan Kabupaten Sukabumi - Lestari, Nurni Arrina; Sri Amelia, Rintan; Antika, Rindi (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
A collaborative program between the Faculty of Economics, Muhammadiyah University of Sukabumi (FE UMMI) and the Regional Revenue Management Center (P3DW) of Sukabumi City and Regency aims to increase tax awareness and compliance among high school students. This activity is implemented through tax socialization, interactive dialogue, and tax payment simulations, presented in an engaging and educational manner. The participatory method allows students to understand the importance of taxes from an early age and their role as the nation's next generation in national development. The results of this activity indicate an increase in students' understanding and positive attitudes toward tax responsibilities. This collaboration represents a form of synergy between educational institutions and the government in fostering a culture of tax awareness in the community, especially among the younger generation. With a more innovative and humane approach, it is hoped that tax awareness will not be merely theoretical but can also be applied in students' daily attitudes and behaviors.